The relation between athletic sports and prevalence of amenorrhea and oligomenorrhea in Iranian female athletes - Dadgostar Haleh; Razi Mohammad; Aleyasin Ashraf; Alenabi Talia; Dahaghin Saeideh (Sports Medicine, Arthroscopy, Rehabilitation, Therapy & Technology, 2009)
Abstract Background In 1992, the concept of female athlete triad was introduced to describe the interrelated problems of amenorrhea, eating disorders and osteoporosis seen in female athletes. To gain a clearer picture of amenorrhea/oligomenorrhea in Iran, one of the main components of the female athlete triad, we therefore established this study on the prevalence of amenorrhea/oligomenorrhea in elite Iranian female athletes, also evaluating the risk factors of these disorders in the same population. Methods This study performed as a cross-sectional study. All elite Iranian female athletes of 34 sports federation, including female athletes in national teams and medalists of Tehran were invited to participate. A total of 788 (95% response rate) returned the questionnaires and were examined. Younger athletes under the age of menarche were excluded. Each athlete completed a self-administered questionnaire, which covered the following questions about participant's demographic information, athletic history, history of injuries and menstrual pattern. In order to diagnose the causes of amenorrhea/Oligomenorrhea including polycystic ovary syndrome(PCOS), participants with amenorrhea/Oligomenorrhea underwent further investigation. They were evaluated by following Para clinic investigation, and an ultrasonographic study of ovary. Results The age ranged from 13–37 (mean = 21.1, SD = 4.5). Seventy one (9.0%) individuals had amenorrhea/oligomenorrhea, among those, 11 (15.5%) had PCOS. There was also a positive association between amenorrhea/oligomenorrhea and the following: age under 20 OR; 2.67, 95%CI(1.47 – 4.85), weight class sports OR; 2.09, 95%CI(1.15 – 3.82), endurance sports OR; 2.89, 95%CI(1.22 – 6.84), late onset of menarche OR; 3.32 95%CI(1.04–10.51), and use of oral contraceptive pills OR; 6.17, 95%CI(3.00 – 12.69). Intensity of training sport or BMI were not risk factors. Conclusion These findings support the previous findings in the literature that the prevalence of amenorrhea/oligomenorrhea is high in athletes. Furthermore, we provided the first report on the prevalence of PCOS in female athletes with amenorrhea/oligomenorrhea. Athletes would be greatly benefited by greater general awareness about the complications of amenorrhea/oligomenorrhea. To increase awareness of exercise-associated menstrual cycle irregularities, it is necessary to design complete and comprehensive education programs for female athletes, their parents, their coaches, and the relevant authorities.